Impact of the COVID-19 pandemic on daily life, mood, and behavior of adults with Down syndrome. Issue 3 (July 2022) - Hartley, Sigan L.; Fleming, Victoria; Piro-Gambetti, Brianna; Cohen, Annie; Ances, Beau M.; Yassa, Michael A.; Brickman, Adam M.; Handen, Benjamin L.; Head, Elizabeth; Mapstone, Mark; Christian, Bradley T.; Lott, Ira T.; et al.
Abstract: Background: The Down syndrome population has been disproportionately affected by Coronavirus 2019 (COVID-19) in terms of experiencing severe illness and death. Societal efforts to curb the spread of COVID-19 may also have taken a heavy toll on the daily lives of individuals with Down syndrome. Objective/hypothesis: The goal of the study was to understand how the COVID-19 pandemic has altered daily life (including residence, employment, and participation in adult disability day programs) and influenced the mood and behavior of adults with Down syndrome. Methods: Between September 2020 and February 2021, caregivers of 171 adults with Down syndrome (aged 22–66 years) located across the United States and in the United Kingdom enrolled in the Alzheimer's Biomarker Research Consortium on Down Syndrome (ABC-DS) completed a survey. Results: The residence of 17% of individuals was altered, and 89% of those who had been employed stopped working during the pandemic. One-third (33%) of individuals were reported to be more irritable or easily angered, 52% were reported to be more anxious, and 41% were reported to be more sad/depressed/unhappy relative to prepandemic. The majority of changes in mood and behavior were of modest severity. Conclusions: The COVID-19 pandemic has had widespread effects on the daily life and mood and behavior of adults with Down syndrome. In the short term, caregivers and providers should be prepared to help adults with Down syndrome with changes in daily routines, residence, employment, or adult disability day programs as society shifts away from COVID-19 safety protocols.